2014
DOI: 10.1371/journal.pone.0103646
|View full text |Cite
|
Sign up to set email alerts
|

An Unclassified Microorganism: Novel Pathogen Candidate Lurking in Human Airways

Abstract: During the assessments of the correlation of the diseases and the microbiota of various clinical specimens, unique 16S ribosomal RNA (rRNA) gene sequences (less than 80% similarity to known bacterial type strains) were predominantly detected in a bronchoalveolar lavage fluid (BALF) specimen from a patient with chronic lower respiratory tract infection. The origin of this unique sequence is suspected to be the causative agent of the infection. We temporarily named the owner organism of this sequence “IOLA” (Inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 46 publications
0
15
0
Order By: Relevance
“…The distinct bacterial communities we observed were consistent with other reports for the swine lung (21) and were consistently reproduced in BEL. These evaluations also led to the observation of an infectious organism present in airways, suggesting that this organism may be of pathogenic concern in swine; moreover, IOLA had previously been reported only in the human respiratory tract in association with clinical disease (23).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The distinct bacterial communities we observed were consistent with other reports for the swine lung (21) and were consistently reproduced in BEL. These evaluations also led to the observation of an infectious organism present in airways, suggesting that this organism may be of pathogenic concern in swine; moreover, IOLA had previously been reported only in the human respiratory tract in association with clinical disease (23).…”
Section: Discussionmentioning
confidence: 99%
“…One bacterial target was based on identification of 16S sequences that did not align with sequences in the SILVA rRNA database. Specifically, IOLA (infectious organism lurking in airways) (22,23) 16S was seen in one of the transplanted and two of the control animals studied. This result was confirmed through cloning and sequencing of additional genomic fragments using published PCR primers (23).…”
Section: Bel Microbiome Developmentmentioning
confidence: 98%
“…NCBI BLAST search ( https://blast.ncbi.nlm.nih.gov ) results revealed that the representative sequence of OTU 30 shared 99.8% similarity with an unclassified bacterium. Recently, the unclassified bacterium was identified in bronchoalveolar lavage fluids (BALFs) in adults with respiratory disease and was temporally named IOLA (Infectious Organism Lurking in Airways) 18 . IOLA was also detected in specimens from patients with respiratory tract disease and in pig lungs 19 21 .…”
Section: Resultsmentioning
confidence: 99%
“…One of the twelve OTUs unclassified at the phylum level using the RDP Classifier showed high similarity with IOLA according to the NCBI BLAST search. We have previously reported that IOLA is a novel microorganism found in BALFs in adults with respiratory disease 18 . This is the first report of IOLA detected in nasal discharge of children.…”
Section: Discussionmentioning
confidence: 96%
“…Dye-labeled DNA sequencing technique is still an important tool for clinical decision making on cancer [3] , [4] , [5] , drug metabolism genotyping [6] , [7] , [8] , pathogen identification [9] , [10] , [11] , inherited disease [12] , [13] , [14] , [15] , [16] , [17] and so on [18] , [19] . However, the methods remain laborious and time-consuming.…”
Section: Datamentioning
confidence: 99%